A polylactic acid fiber composite carrier for drug delivery, preparation method and application
PLGA fibers with cavity were prepared by coaxial electrospinning technology and cross-linked with quaternized chitosan to form a gel composite carrier, which solved the problem of mismatch in the mechanical properties of existing brain local drug delivery materials, and achieved the sequential release of drugs and the protection of brain tissue.
Patent Information
- Application Number
- CN202410939189.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-07-15
- Publication Date
- 2025-04-04
- Estimated Expiration
- 2044-07-15
AI Technical Summary
The stiffness of existing local brain drug delivery materials is much greater than that of brain tissue, resulting in foreign body reactions, immune responses and mechanical damage, and cannot effectively match the mechanical properties of brain tissue.
Polylactic acid-glycolic acid (PLGA) fibers were prepared by coaxial electrospinning technology, and mixed with quaternized chitosan solution to form a PLGA fiber gel composite carrier through cross-linking reaction, and combined with aqueous glycerol solution to form multi-stage structural fibers with cavity.
The timing and slow release of drugs are achieved, the brain tissue is protected from mechanical damage, and matched with the mechanical properties of brain tissue, broadening the application of local drug delivery intracranially.
Smart Images

Figure CN118845631B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of polymer local drug delivery materials, and in particular relates to a polylactic acid fiber composite carrier for drug delivery, a preparation method and an application thereof. Background Art
[0002] The brain is the softest organ in the body, with a modulus of less than 10 3 Pa, local drug delivery implant materials used for brain tumor treatment will trigger foreign body reactions, produce severe immune reactions and rejection reactions during use due to the mismatch between their mechanical properties and brain tissue; at the same time, due to the limitations of the material preparation process, the viscoelasticity of brain implant materials is poor and the rigidity is high. After the materials are implanted, they will cause mechanical damage to the healthy brain parenchyma, further aggravating the lesions. Therefore, it is very important to prepare a local drug delivery carrier that matches the mechanical properties of brain tissue.
[0003] At present, hydrogel materials are widely used as local drug delivery materials because of their controllable mechanical properties and ability to meet the mechanical environment of different biological tissues. However, due to the low drug loading capacity of hydrogels for many hydrophobic therapeutic drugs and the fast degradation time of hydrogels, it is impossible to achieve on-demand and slow release of drugs at the lesion site, which limits the application of hydrogels in local drug delivery systems.
[0004] Polylactic-co-glycolic acid (PLGA) is widely used in drug delivery systems due to its good biosafety and degradation performance. PLGA electrospun fibers with a cavity structure prepared by coaxial electrospinning technology can be loaded with hydrophilic and hydrophobic drugs for local administration. After entering the physiological environment, the cavity structure of the PLGA fiber swells due to water absorption, first releasing the drugs loaded in the cavity, and then the drugs in the PLGA fiber matrix are slowly released, realizing the timed slow release of the drugs. However, after the PLGA fiber membrane is locally implanted in the brain tumor site, the mechanical properties do not match those of the brain tissue, and the PLGA fiber membrane will cause mechanical damage to the healthy brain parenchyma, which is not conducive to the prognosis of the disease.
[0005] Therefore, PLGA fiber and gel are combined, and the advantages of both are utilized to prepare a PLGA fiber gel composite drug carrier with mechanical properties matching those of brain tissue, thereby protecting brain tissue from mechanical damage. At the same time, the carrier can load drugs or biological factors with different properties and realize the timed release of drugs, thus meeting the drug administration needs at different stages of brain tumor treatment. Therefore, there is an urgent need for a polylactic acid fiber composite carrier for drug delivery, a preparation method and an application. Summary of the invention
[0006] In view of the problem that the stiffness of the brain local drug delivery material in the prior art is much greater than that of the brain tissue and does not match the mechanical properties of the brain tissue, the present invention provides a method for preparing a polylactic acid fiber composite carrier for drug delivery:
[0007] S1: dissolving a polylactic acid-glycolic acid copolymer in a mixed solvent to obtain a polylactic acid-glycolic acid solution, using the polylactic acid-glycolic acid solution as an external phase and a glycerol aqueous solution as an internal phase, and performing coaxial electrospinning to obtain polylactic acid-glycolic acid fibers;
[0008] S2: The polylactic acid-glycolic acid fiber obtained in S1 and the quaternized chitosan solution are mixed to obtain a mixed solution, and the sodium carbonate solution is added to the mixed solution for cross-linking to obtain a polylactic acid-glycolic acid fiber gel composite carrier.
[0009] Furthermore, the mixed solvent described in S1 is dichloromethane and dimethyl carbonate in a mass ratio of 8:2.
[0010] Furthermore, in the coaxial electrospinning described in S1, the inner phase pushing speed is 0.1-0.25 mL / h, the outer phase pushing speed is 1.0 mL / h, the voltage is 15.67 kV, the ambient temperature is 40-45° C., and the humidity is 30%.
[0011] Furthermore, the mass ratio of the polylactic acid-glycolic acid fiber and the quaternized chitosan described in S2 is 1:1.
[0012] A polylactic acid fiber composite carrier for drug delivery, wherein the polylactic acid fiber composite carrier for drug delivery is a cavity structure.
[0013] The invention discloses an application of a polylactic acid fiber composite carrier for drug delivery. The polylactic acid fiber composite carrier is applied in preparing a carrier for intracranial drug delivery.
[0014] Technical Effects
[0015] (1) Advantages of the preparation method: The present invention provides a method for preparing a polylactic acid fiber composite carrier for drug delivery. The present invention adopts coaxial electrospinning, which is divided into an inner phase solution and an outer phase solution. The physicochemical properties of the inner and outer phase solutions can be completely different. Therefore, drugs of different properties can be loaded into the inner and outer phase solutions at the same time, thereby protecting the activity and function of biological therapeutic factors from being destroyed.
[0016] (2) Advantages of the carrier: The polylactic acid fiber composite carrier for drug delivery provided by the present invention has a multi-level structure fiber with a cavity. The cavity structure allows the glycerol to absorb water and burst first, releasing the internal phase drug, and then the fiber matrix slowly degrades to release the drug loaded in the fiber matrix, thereby achieving timed release of drugs, as well as step-by-step release and slow release.
[0017] (3) Application: The polylactic acid fiber composite carrier for drug delivery provided by the present invention can protect the healthy brain parenchyma from being damaged during the process of local intracranial drug delivery, thereby broadening the application of intracranial drug delivery. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:
[0019] Figure 1 This is a schematic diagram of the preparation process of the PLGA fiber gel composite carrier of the present invention;
[0020] Figure 2 This is a fluorescence image of the PLGA fiber with a cavity structure according to Example 1 of the present invention;
[0021] Figure 3 is a scanning electron microscope image of the PLGA fiber of Example 1 of the present invention;
[0022] Figure 4 This is a statistical diagram of the fiber diameter of the PLGA fiber of Example 1 of the present invention;
[0023] Figure 5 This is a scanning electron microscope image of the PLGA fiber gel composite carrier of Example 1 of the present invention;
[0024] Figure 6 This is a graph of the rheological properties of the PLGA fiber composite gel carrier of Example 1 of the present invention;
[0025] Figure 7 This is a diagram of the step-by-step degradation process of the PLGA fiber composite gel carrier of Example 1 of the present invention;
[0026] Figure 8 This is a schematic diagram of the cavity of the PLGA multi-level structure fiber with cavity in Example 1 of the present invention. DETAILED DESCRIPTION
[0027] The following will be combined with Examples 1 to 3 of the present invention and the attached Figures 1 to 8 , the technical solution of the present invention is clearly and completely described. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] Combination Figure 1 The present invention provides a method for preparing a polylactic acid fiber composite carrier for drug delivery, comprising the following steps:
[0029] S1: First, poly(lactic acid-co-glycolic acid) copolymer is dissolved in a mixed solvent of dichloromethane (DCM) and dimethyl carbonate (DMC) to form an 18% PLGA solution, and then a coaxial electrospinning technique is used, the PLGA solution is used as the external phase of coaxial electrospinning, and a 70% glycerol aqueous solution is used as the internal phase solution of coaxial electrospinning, and electrospinning is performed, and then the electrospinning parameters are adjusted, including the internal phase pushing speed, the external phase pushing speed, the voltage, the ambient temperature, and the humidity; and a PLGA fiber with a cavity structure is obtained;
[0030] S2: PLGA fibers and 4% quaternary ammonium chitosan solution are mixed in a mass ratio of 1:1 to obtain a mixed solution, and then sodium carbonate solution is added to the mixed solution for cross-linking to obtain a PLGA fiber gel composite carrier.
[0031] Example 1
[0032] S1: Polylactic acid-glycolic acid copolymer (50:50, Mw 38000-54000) was dissolved in a mixed solvent of dichloromethane (DCM) and dimethyl carbonate (DMC) to form an 18% PLGA solution, and coaxial electrospinning was used, and the PLGA solution was used as the external phase of coaxial electrospinning; 70% glycerol aqueous solution was used as the internal phase solution of coaxial electrospinning, and electrospinning was performed, and the internal phase push speed was set to 0.1mL / h, the external phase push speed was 1.0mL / h, and the voltage was 15.67kV. The ambient temperature was 40℃ and the humidity was 30%, and PLGA fibers with a cavity structure were obtained;
[0033] S2: PLGA fibers and 4% quaternary ammonium chitosan solution were mixed at a mass ratio of 1:1 to obtain a mixed solution, and then 50 μL of a 30 pM sodium carbonate solution was added to perform cross-linking to obtain a PLGA fiber gel composite carrier.
[0034] Combination Figure 2The PLGA fiber structure obtained in Example 1 is a multi-level structure fiber with a cavity. The inner phase glycerol solution is loaded with hydrophilic rhodamine B, and the outer phase PLGA solution is loaded with hydrophobic coumarin 6. Under the observation of a fluorescence microscope, it is confirmed that the glycerol solution forms a cavity in the fiber, and it is confirmed that the multi-level structure fiber with a cavity can be prepared by coaxial electrospinning technology. PLGA forms a fiber matrix. Combined Figure 3 and Figure 4 The scanning electron microscope image of PLGA fiber and the statistical graph of fiber diameter can be obtained. From the scanning electron microscope image, it can be seen that the fiber diameter is evenly distributed and the diameter is 1.2 microns, indicating that PLGA fiber is successfully prepared by electrospinning technology.
[0035] Combination Figure 8 Under physiological conditions, the cavity of the multi-level structure fiber with a cavity structure is first burst due to the absorption of water by glycerol, releasing the internal phase drug, and then the fiber matrix slowly degrades to release the drug loaded in the fiber matrix, realizing the timed release of the drug.
[0036] Combination Figure 5 The microstructure of PLGA can be obtained from Figure 5 It can be seen that PLGA fibers are wrapped by gel, and this structure can combine the advantages of fiber timed drug release and the soft mechanical properties of gel, matching the mechanical properties of brain tissue, and local implantation of drug-loaded carriers does not cause mechanical damage to brain tissue. Figure 6 The mechanical properties of the PLGA fiber gel composite carrier were tested by rotational rheometer. It was found that the storage modulus G' and loss modulus G" of the PLGA fiber gel composite carrier were both lower than 10 3 Pa, which matches the modulus of brain tissue.
[0037] Combination Figure 7 It can be seen that first, the gel degrades to release the drugs loaded in the gel. In this process, the hydrogel is surface-dissolved and the fibers are gradually exposed from the fibers. Then, the cavity structure of the PLGA fiber absorbs water and swells to release the drugs loaded in the cavity. In this process, the cavity inside the fiber ruptures, and the scanning electron microscope shows that there are holes on the surface of the fiber. Finally, the fiber matrix PLGA slowly degrades to release the drugs loaded in the fiber matrix. In this process, the PLGA undergoes bulk degradation. Therefore, the PLGA fiber gel composite carrier can continue to release the drugs step by step and slowly.
[0038] Example 2
[0039] S1: Polylactic acid-glycolic acid copolymer (50:50, Mw 38000-54000) was dissolved in a mixed solvent of dichloromethane (DCM) and dimethyl carbonate (DMC) to form an 18% PLGA solution, and coaxial electrospinning was used, and the PLGA solution was used as the external phase of coaxial electrospinning; 70% glycerol aqueous solution was used as the internal phase solution of coaxial electrospinning, and electrospinning was performed, and the internal phase push speed was set to 0.25mL / h, the external phase push speed was 1.0mL / h, and the voltage was 15.67kV. The ambient temperature was 45°C and the humidity was 30%, and PLGA fibers with a cavity structure were obtained;
[0040] S2: PLGA fibers and 4% quaternary ammonium chitosan solution were mixed at a mass ratio of 1:1 to obtain a mixed solution, and then 50 μL of a 30 pM sodium carbonate solution was added to perform cross-linking to obtain a PLGA fiber gel composite carrier.
[0041] Example 3
[0042] S1: Polylactic acid-glycolic acid copolymer (50:50, Mw 38000-54000) was dissolved in a mixed solvent of dichloromethane (DCM) and dimethyl carbonate (DMC) to form an 18% PLGA solution, and coaxial electrospinning was used, and the PLGA solution was used as the external phase of coaxial electrospinning; 70% glycerol aqueous solution was used as the internal phase solution of coaxial electrospinning, and electrospinning was performed, and the internal phase push speed was set to 0.2mL / h, the external phase push speed was 1.0mL / h, and the voltage was 15.67kV. The ambient temperature was 43°C and the humidity was 30%, and PLGA fibers with a cavity structure were obtained;
[0043] S2: PLGA fibers and 4% quaternary ammonium chitosan solution were mixed at a mass ratio of 1:1 to obtain a mixed solution, and then 50 μL of a 30 pM sodium carbonate solution was added to perform cross-linking to obtain a PLGA fiber gel composite carrier.
[0044] The present invention provides a method for preparing a polylactic acid fiber composite carrier for drug delivery. The coaxial electrospinning technology is adopted, and drugs of different properties can be simultaneously loaded in the inner and outer phase solutions. The outer phase in the present invention is a PLGA solution, and some hydrophobic chemotherapy drugs can be loaded in the outer phase, such as temozolomide, a chemotherapy drug for treating glioblastoma. The inner phase of the PLGA fiber is a glycerol aqueous solution, and hydrophilic therapeutic factors, such as antibodies, proteins, and CAR-T cells, can be loaded to protect the activity and function of these biological therapeutic factors from being destroyed.
[0045] The present invention provides a polylactic acid fiber composite carrier for drug delivery. The PLGA fiber structure obtained by the preparation method of the present invention is a multi-level structure fiber with a cavity. Under a physiological environment, the cavity of the multi-level structure fiber with a cavity structure is first burst due to glycerol absorbing water, releasing the internal phase drug, and then the fiber matrix slowly degrades to release the drug loaded in the fiber matrix, thereby realizing the sequential release of the drug. In addition, the obtained PLGA fiber gel can combine the advantages of the fiber sequential release of drugs with the soft mechanical properties of the gel, match the mechanical properties of the brain tissue, and does not cause mechanical damage to the brain tissue after the drug-carrying carrier is locally implanted.
[0046] The present invention provides an application of a polylactic acid fiber composite carrier for drug delivery. Through the characteristics of the polylactic acid fiber composite carrier, during the process of local intracranial drug delivery, not only can the healthy brain parenchyma be protected from damage, but also the time-sequential slow release of the drug can be achieved, thereby achieving the purpose of long-term drug administration, and broadening the application of intracranial drug delivery.
Claims
1. A method for preparing a polylactic acid fiber composite carrier for drug delivery, characterized in that: S1: dissolving a polylactic acid-glycolic acid copolymer in a mixed solvent to obtain a polylactic acid-glycolic acid solution, using the polylactic acid-glycolic acid solution as an external phase and a glycerol aqueous solution as an internal phase, and performing coaxial electrospinning to obtain polylactic acid-glycolic acid fibers; S2: The polylactic acid-glycolic acid fiber obtained in S1 and the quaternized chitosan solution are mixed to obtain a mixed solution, and a sodium carbonate solution is added to the mixed solution for cross-linking to obtain a polylactic acid-glycolic acid fiber gel composite carrier; The mixed solvent described in S1 is dichloromethane and dimethyl carbonate in a mass ratio of 8:
2.
2. The method for preparing a polylactic acid fiber composite carrier for drug delivery according to claim 1, characterized in that: In the coaxial electrospinning described in S1, the inner phase pushing speed is 0.1-0.25 mL / h, the outer phase pushing speed is 1.0 mL / h, the voltage is 15.67 kV, the ambient temperature is 40-45° C., and the humidity is 30%.
3. The method for preparing a polylactic acid fiber composite carrier for drug delivery according to claim 1, characterized in that: The mass ratio of the polylactic acid-glycolic acid fiber and the quaternized chitosan described in S2 is 1:
1.
4. A polylactic acid fiber composite carrier for drug delivery obtained by the preparation method according to any one of claims 1 to 3, characterized in that: The polylactic acid fiber composite carrier for drug delivery is a cavity structure.
5. The use of a polylactic acid fiber composite carrier for drug delivery according to claim 4, characterized in that: The polylactic acid fiber composite carrier is used in preparing a carrier for intracranial drug delivery.
Citation Information
Patent Citations
Preparation method of drug-loaded nano fiber membrane
CN107157960A
Double-drug-loaded nanofiber hydrogel composite cartilage repair system and preparation method thereof
CN113941033A